Tubers and its role in historic political fragmentation in Africa - Nonso Obikili (African Economic History Network (AEHN), 2023)
This paper examines the link between historical political fragmentation and surplus agricultural production, and the impact of natural endowments with regards to crop suitability. I show that in sub-Saharan Africa, groups that cultivated tubers, specifically yams, were more likely to have higher levels of local political fragmentation. I show that both tubers and most cereals were positively correlated with historic population density and that there was no historic discrimination in the capacity of crops to produce surpluses and support large populations. I however show that unlike cereal cultivators who were more likely to be centralized, tuber cultivators were likely to have more local political fragmentation. I use crop suitability and the proximity to the area of the domestication of yams to show that cultivating yams did lead to more local political fragmentation. I argue that this is likely due to the biological properties of yams which make them more difficult to expropriate and implies that surpluses stay local. I argue that the experience of keeping surpluses local is associated with contemporary social norms that are against autocracy and unitary accumulation of power. These social norms are an example of the mechanism through which these historical institutional structures transmit to contemporary times.
Keywords: O10; N47; N57; D72; 330; Political Fragmentation; Agriculture; Social Norms; Africa